Lembaga Pendidikan Pesantren dan Tantangan Global - Imam Faizin (Madaniyah, 2020)
In the modernization era, pesantren as one of the Islamic educational institutions can not only be silent and run traditional learning methods and systems, if they do not want to be left behind. Therefore, pesantren need a lot of changes in meeting the demands of the times. Various ideas and opinions also emerged along with the start of modernization in the world of pesantren. However, pesantren still cannot be fully reconstructed by modernism in Indonesia. Because pesantren, besides being the oldest Islamic education institution in Indonesia, is also a cultural asset of the nation that is religious in nature. This can be seen from the existence of elements of cultural originality, such as pesantren buildings, dormitory systems, several types of teaching that are absorbed from certain regional cultures and so on. So pesantren in the modernization era face a very heavy dilemma, on the one hand he must try to adjust to the changing times that require him to leave the traditional systems and methods. On the other hand he must maintain the nation's sublime culture that is identical with religiosity and norms so as not to participate in the plagiarization of Western culture.